2011
DOI: 10.1089/pop.2010.0001
|View full text |Cite
|
Sign up to set email alerts
|

Improving Population Care with an Integrated Electronic Panel Support Tool

Abstract: This study measured the impact of an electronic Panel Support Tool (PST) on primary care teams' performance on preventive, monitoring, and therapeutic evidence-based recommendations. The PST, tightly integrated with a comprehensive electronic health record, is a dynamic report that identifies gaps in 32 evidence-based care recommendations for individual patients, groups of patients selected by a provider, or all patients on a primary care provider's panel. It combines point-of-care recommendations, disease reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Previous studies have demonstrated that optimizing the use of electronic health records in this way benefits our members' health. 26,27 The current model suggests that it is also good for the environment.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have demonstrated that optimizing the use of electronic health records in this way benefits our members' health. 26,27 The current model suggests that it is also good for the environment.…”
Section: Discussionmentioning
confidence: 86%
“…Sources vary for chronic conditions' diagnoses and utilization data; for example, they may include point-of-care panel management tools and enterprise data warehouses. 11,12 Other clinical data can be found in the electronic health record (EHR)-KP HealthConnect-and include encounter diagnoses, the use of home oxygen and home hospital beds, surgeries and procedures, severe organ failure, and hospice or palliative care orders. In addition, risk scores and indicators have been tailored to specifications in individual KP Regions, and regional implementation can add data specifically available and valuable to that Region.…”
Section: Algorithm Developmentmentioning
confidence: 99%
“…This reminder would prompt front desk staff to talk with patients about their health insurance expiration date and/or facilitate referrals to appropriate resources within (eg, enrollment specialists or clinic staff who specialize in coverage assistance) or outside (eg, state or federal websites and local agencies available to assist patient with health insurance enrollment) the clinic. 9,[15][16][17][18][19][20] For clinics that ask about health insurance information before a visit, tools could be tailored to identify scheduled patients without coverage and facilitate communication between the enrollment specialist and patient regarding their potential options to gain insurance. In addition, EHR tools could create customized messages about potential insurance plans available to the patient (if uninsured), or enrollment expiration dates (if insured), to be included with the after-visit summary.…”
Section: Enrollment Specialistmentioning
confidence: 99%
“…These confluent events yield an unprecedented opportunity to use clinical data and functions in novel ways. [15][16][17][18][19][20] Although some clinics already engage in health insurance outreach activities and insurance coverage discussions with patients, these efforts are not usually supported by HIT or HIE. We anticipate that many health care organizations will embrace having enhanced capacity to help their patients obtain and keep coverage because of the benefits to be gained from having stably insured patients.…”
mentioning
confidence: 99%